Decoupling Between Diastolic Pulmonary Artery Pressure and Pulmonary Capillary Wedge Pressure as a Prognostic Factor After Continuous Flow Ventricular Assist Device Implantation - Imamura, Teruhiko (Circ Heart Fail, 2017)
BACKGROUND: A cohort of heart failure (HF) patients receiving left ventricular assist devices (LVADs) has decoupling of their diastolic pulmonary artery pressure and pulmonary capillary wedge pressure. However, the clinical implications of this decoupling remain unclear. METHODS AND RESULTS: In this prospective study, patients with LVADs underwent routine invasive hemodynamic ramp testing with right heart catheterization, during which LVAD speeds were adjusted. Inappropriate decoupling was defined as a >5 mm Hg difference between diastolic pulmonary artery pressure and pulmonary capillary wedge pressure. The primary outcomes of survival and heart failure readmission rates after ramp testing were assessed. Among 63 LVAD patients (60±12 years old and 25 female [40%]), 27 patients (43%) had inappropriate decoupling at their baseline speed. After adjustment of their rotation speed during ramp testing, 30 patients (48%) had inappropriate decoupling. Uni/multivariable Cox analyses demonstrated that decoupling was the only significant predictor for the composite end point of death and heart failure readmission during the 1 year following the ramp study (total of 18 events; hazards ratio, 1.09; 95% confidence interval, 1.04–1.24; P<0.05). Furthermore, normalization of decoupling (n=8) during ramp testing was significantly associated with higher 1-year heart failure readmission–free survival rate compared with the non-normalized group (n=19, 100% versus 53%; P=0.035). CONCLUSIONS: The presence of inappropriate decoupling was associated with worse outcomes in patients with LVADs. Prospective, large-scale multicenter studies to validate the result are warranted.